Obtaining an agglomerate for construction material from an adhesive obtained from wet blue chip from the leather tanning process. - Miguel Valdez-Urbina (2019)
The leather tanning industry produces a large amount of wastewater and solid waste containing a significant amount of chromium, the wet blue chip is a solid micro-cocoa particulate material impregnated with chromium synthetic oil and grease and tanning agents. The objective of the study was to investigate the production of an agglomerate from an adhesive obtained from the wet blue chip produced by alkaline hydrolysis at 60 ° C temperature, 0.4N NaOH and 4 hrs. for neutralization. To obtain the agglomerate, 2 kg of sawdust of 1 mm of ebony wood was used, which was dried at 105 ° C for 4 hours, then manual mixing was carried out in two proportions; 125 g of adhesive and 250 g of sawdust (0.5 / 1), and a second proportion of 250 g of adhesive and 250 g of sawdust (1/1), the mixtures were carried out for 20 minutes at room temperature, the pressing was cold at 100kg / cm2, in stainless steel molds to avoid stickingthe agglomerate, the samples remained in the press for 2 hrs., after the pressing the samples were exposed to the environment in a place with solar incidence, where they remained in the mold for the next 48 hrs. At the end of this time the samples were removed from the mold to be exposed to the sun for 5 days, the agglomerate obtained was subjected to mechanical tests such as the compressive strength in a universal breaking machine according to DIN 68763 for "boards particle plans for use in concepts of building construction, requirements, testing and inspection", were also subjected to the thermal conductivity test according to ASTM C-177 in a thermal gradient emitted by a 1200-watt plate, measuring the temperature passed every 5 minutes, and the apparent density test according to DIN 68763. The results showed in the thermal conductivity tests that the mixture 1/1 (250gr of adhesive and 250g of sawdust), presented lower average than the ASTM C-177 standard (0.28W / mK) with an average of 0.22 W / mK, in addition this mixture presented higher compressive strength than DIN 68763 (175Kgf / m2) with a an average of 291.57 Kgf / m2, proving to be a very resistant agglomerate for construction and representing an eco-friendly solution for the final disposal of the wet blue chip, from the leather tanning process.